2021
DOI: 10.1002/npr2.12176
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic suppression of anterior cingulate cortical neurons projecting to the visual cortex disrupts attentional behavior in mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…While our previous studies have shown that ACA VIS projection neurons are required for attentional behavior during 5CSRTT in mice ( Norman et al, 2021a , b ), it is unknown whether the contribution of this subpopulation of frontal cortex projecting neurons are task demand dependent. To this end, we selectively suppressed ACA VIS axon terminal activity in visual cortex using the inhibitory opsin halorhodopsin eNpHR3.0 at key time points during both the 5CSRTT and 2CSRTT in which the stimulus duration length was shuffled between 2 and 1 s in a pseudorandomized order to determine its effect on task performance ( Figures 3A,B ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…While our previous studies have shown that ACA VIS projection neurons are required for attentional behavior during 5CSRTT in mice ( Norman et al, 2021a , b ), it is unknown whether the contribution of this subpopulation of frontal cortex projecting neurons are task demand dependent. To this end, we selectively suppressed ACA VIS axon terminal activity in visual cortex using the inhibitory opsin halorhodopsin eNpHR3.0 at key time points during both the 5CSRTT and 2CSRTT in which the stimulus duration length was shuffled between 2 and 1 s in a pseudorandomized order to determine its effect on task performance ( Figures 3A,B ).…”
Section: Resultsmentioning
confidence: 91%
“…These findings support a model that the frontal-sensory ACA VIS projection regulates visual attention behavior during specific high task demand conditions. Previous studies in mice revealed a causal role of a specific sub-population ACA neurons projecting to the visual cortex in contributing to attentional behavior ( Norman et al, 2021a , b ), similar to other ACA neurons ( Kim et al, 2016 ; White et al, 2018 ). However, it remained unclear whether this mechanism was dependent on task demand.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We hypothesize that the 5CSRTT may be used in the future as a behavioral readout of prefrontal circuit function in Ube3a m−/p+ mice. In rodents, the activity of ACC, a prefrontal subregion, is tightly linked to omissions on the 5CSRTT (Chudasama et al, 2003;Koike et al, 2016;Norman et al, 2021), though other circuits beyond ACC also contribute to attentional processing on the 5CSRTT and related tasks (Chudasama et al, 2012;Aoki et al, 2015;Kim et al, 2016;Wulaer et al, 2020). Future work may test the hypothesis that manipulating Ube3a levels in ACC neurons will selectively affect omissions on the 5CSRTT.…”
Section: Discussionmentioning
confidence: 99%
“…The light cue has a fixed short duration, and the number of trials omitted ("omissions") provides a readout of attention, while the number of premature responses during an intertrial interval provides a readout of impulsivity. Lesion studies and chemogenetic manipulations have demonstrated that rodent ACC regulates attentional performance during the 5CSRTT (Chudasama et al, 2003;Koike et al, 2016;Norman et al, 2021). The 5CSRTT has been widely used in rodent models of a variety of neurodevelopmental and neuropsychiatric disorders, including autism, addiction, and attention deficit hyperactivity disorder (Kramvis et al, 2013;Lloyd et al, 2013;Dommett, 2014;Anshu et al, 2017;Caballero-Puntiverio et al, 2017;Justinussen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%